2017
DOI: 10.4314/ijbcs.v10i5.9
|View full text |Cite
|
Sign up to set email alerts
|

Niveau de connaissance et composition minérale de Hydrocotyle bonariensis Lam. (Araliaceae), une plante utilisée dans les ménages du District d’Abidjan (Côte d’Ivoire)

Abstract: RESUME ABSTRACTHydrocotyle bonariensis is a plant species entering in food and medicinal habits of people in Cote d'Ivoire. This work was conducted to determine the households' knowledge and utilization of this plant in the district of Abidjan as well as it mineral content. A total of 800 households in six settings were interviewed using a questionnaire. The determination of mineral content was carried out using an atomic adsorption spectrophotometer. The surveyed people included 597 women and 203 men. Their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…All these virtues recognized by "conôro" could classify it as a functional food. Studies conducted on other condiments and species with significant socio-economic value in the sub-region confirm these findings (Fandohan et al, 2010;Kim et al, 2016;Najafi et al, 2016;Monyn et al, 2016). The study conducted among the populations revealed seven types of "conôro".…”
Section: Discussionsupporting
confidence: 61%
“…All these virtues recognized by "conôro" could classify it as a functional food. Studies conducted on other condiments and species with significant socio-economic value in the sub-region confirm these findings (Fandohan et al, 2010;Kim et al, 2016;Najafi et al, 2016;Monyn et al, 2016). The study conducted among the populations revealed seven types of "conôro".…”
Section: Discussionsupporting
confidence: 61%
“…The high proportion of women could be justified by the rural character of the survey and by the culture of women to cook. Monyn et al [18] and Kouakou et al [19] confirm this hypothesis by reporting that in Côte d'Ivoire, as in all African societies, women perform household tasks and spend more time. Beagan et al [20] have shown that women's involvement in food tasks is due to the fact that women themselves have chosen food work because it is easier or prefer to cook for reasons of quality, cleanliness and family health.…”
Section: Discussionmentioning
confidence: 89%
“…Saponosides have surfactant, antifungal, antibacterial and antiviral properties, they exhibit vein and capillary protective activities and then edematous activity with hormonal activity [23]. The richness of secondary metabolites of H. bonariensis could explain the wide spectrum of its medicinal use and scientifically proven pharmacological properties [1,10,11,13,25,29,32]. The results of the cell toxicity test applied on Artemia salina shrimp larvae revealed variability in lethality rate, observed according to the different concentrations used.…”
Section: Discussionmentioning
confidence: 99%